The Influence of Islamic Organization Culture, Interpersonal Communication, Rewards, and Punishments on Employee Performance - Kamilah, Haflatul; Hastriana, Anna Zakiyah (Program Studi Manajemen Keuangan Syariah, 2025)
This study is driven by the critical role of employee performance—defined as the capability and effort of workers to meet organizational standards—in the success of Islamic financial institutions, particularly BMT NU in Madura. BMT NU operates with distinct cultural, religious, and ethical values that may differentially influence employee performance compared to conventional institutions. Factors such as Islamic Organizational Culture, Interpersonal Communication, Reward, and Punishment are examined for their impact on employee performance. These factors influence employee performance because Islamic organizational culture provides ethical guidance and motivation, interpersonal communication enhances collaboration and clarity, rewards boost morale and productivity, and punishments enforce discipline and accountability, all of which collectively shape a conducive work environment. Using an exploratory research design with a quantitative descriptive approach, the study surveyed 78 employees who had worked at BMT NU in Madura for at least six months, selected through purposive sampling. Data was collected via questionnaires and analyzed using multiple linear regression in SPSS version 23. The findings reveal that Islamic culture (t=3.008), communication (t=2.279), rewards (t=2.229), and punishments (t=2.245) significantly affect performance (t-table=1.665). Simultaneously, F-count=30.905 > F-table=2.730, with R²=0.629 (62.9% variance explained). The research affirms that proper management of these factors is crucial for optimizing Islamic organizations' performance, recommending that BMT NU in Madura enhance Islamic culture and communication through religious training and team building while implementing a transparent Sharia-based reward-punishment system with fair evaluations and constructive feedback to sustain high employee performance.